To find the y-values for the line given by the equation \( y = 2x + 3 \), we can substitute the x-values into the equation.
Let's calculate the y-values for the specified x-values:
-
For \( x = 0 \): \[ y = 2(0) + 3 = 0 + 3 = 3 \] So, the first point is \( (0, 3) \).
-
For \( x = 2 \): \[ y = 2(2) + 3 = 4 + 3 = 7 \] So, the second point is \( (2, 7) \).
-
For \( x = 3 \): \[ y = 2(3) + 3 = 6 + 3 = 9 \] So, the third point is \( (3, 9) \).
-
For \( x = 4 \): \[ y = 2(4) + 3 = 8 + 3 = 11 \] So, the fourth point is \( (4, 11) \).
-
For \( x = 5 \): \[ y = 2(5) + 3 = 10 + 3 = 13 \] So, the fifth point is \( (5, 13) \).
Now we can fill in the blanks based on these calculations:
- The blank for \( 2(2) + 3 \) should be \( 7 \) (answer choice H).
- The blank for \( 2(3) + 3 \) should be \( 9 \) (answer choice D).
- The blank for \( 2(4) + 3 \) should be \( 11 \) (answer choice A).
- The blank for \( 2(5) + 3 \) should be \( 13 \) (answer choice F).
Here's the final filled-in information:
- For \( x = 2 \): \( 2(2) + 3 = 7 \) (Fill in: 7)
- For \( x = 3 \): \( 2(3) + 3 = 9 \) (Fill in: 9)
- For \( x = 4 \): \( 2(4) + 3 = 11 \) (Fill in: 11)
- For \( x = 5 \): \( 2(5) + 3 = 13 \) (Fill in: 13)
Thus, the answers for all the blanks are:
- For \( blank \) when \( x = 2 \): 7 (H)
- For \( blank \) when \( x = 3 \): 9 (D)
- For \( blank \) when \( x = 4 \): 11 (A)
- For \( blank \) when \( x = 5 \): 13 (F)